Ischemic postconditioning may not influence early brain injury induced by focal cerebral ischemia/reperfusion in rats - Yoo Kyung Kim (Korean Journal of Anesthesiology, 2010)
BackgroundExperimental studies have shown that ischemic postconditioning can reduce neuronal injury in the setting of cerebral ischemia, but the mechanisms are not yet clearly elucidated. This study was conducted to determine whether ischemic postconditioning can alter expression of heat shock protein 70 and reduce acute phase neuronal injury in rats subjected to transient focal cerebral ischemia/reperfusion.MethodsFocal cerebral ischemia was induced by intraluminal middle cerebral artery occlusion for 60 min in twenty male Sprague-Dawley rats (250-300 g). Rats were randomized into control group and an ischemic postconditioning group (10 rats per group). The animals of control group had no intervention either before or after MCA occlusion. Ischemic postconditioning was elicited by 3 cycles of 30 s reperfusion interspersed by 10 s ischemia immediately after onset of reperfusion. The infarct ratios, brain edema ratios and motor behavior deficits were analyzed 24 hrs after ischemic insult. Caspase-3 reactive cells and cells showing heat shock protein 70 activity were counted in the caudoputamen and frontoparietal cortex.ResultsIschemic postconditiong did not reduce infarct size and brain edema ratios compared to control group. Neurologic scores were not significantly different between groups. The number of caspase-3 reactive cells in the ischemic postconditioning group was not significantly different than the value of the control group in the caudoputamen and frontoparietal cortex. The number of cells showing heat shock protein 70 activity was not significantly different than the control group, as well.ConclusionsThese results suggest that ischemic postconditioning may not influence the early brain damage induced by focal cerebral ischemia in rats.